2017
DOI: 10.1177/000313481708300614
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Geriatric Trauma Patients on Preinjury Anticoagulation: A Multicenter Study

Abstract: Outpatient anticoagulation in the geriatric trauma patient is a challenging clinical problem. The aim of this study is to determine clinical outcomes associated with class of preinjury anticoagulants (PA) used by this population. This is a multicenter retrospective cohort study among four Level II trauma centers. A total of 1642 patients were evaluated; 684 patients were on anticoagulation and 958 patients were not. Patients on PA were compared with those who were not. Drug classes were divided into thromboxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Even with the availability of both preinjury and hospital data, we were unable to generate a risk indicator that provided both high sensitivity and specificity in predicting mortality. Many variables typically considered in “high‐risk” patients (e.g., anticoagulant use, skilled nursing facility residence prior to trauma and specific anatomic injuries) were not predictive of mortality in this analysis …”
Section: Discussionmentioning
confidence: 94%
“…Even with the availability of both preinjury and hospital data, we were unable to generate a risk indicator that provided both high sensitivity and specificity in predicting mortality. Many variables typically considered in “high‐risk” patients (e.g., anticoagulant use, skilled nursing facility residence prior to trauma and specific anatomic injuries) were not predictive of mortality in this analysis …”
Section: Discussionmentioning
confidence: 94%
“…This agrees with previous studies, like Fortuna et al, who showed age was a significant predictor of mortality in blunt head injury. 2,5,14,16 Discharge to Facility…”
Section: Mortalitymentioning
confidence: 99%
“…1 It is believed that novel oral anticoagulants (NOACs) hold a lower risk of adverse events compared with vitamin K antagonists. [2][3][4][5][6] In Ang's study on geriatric trauma, NOACs tended to have the least number of complications, while platelet P2Y12 inhibitors stood out with the most adverse events and the highest risk of intracranial hemorrhage (ICH). 5 To counteract the risk of bleeding, reversal agents are available for most anticoagulants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between patients with and without aspirin in spleen injury and the results after propensity score matching. or the need for blood transfusions (15)(16)(17)25). Regarding chest trauma, one series demonstrated that antiplatelet or anticoagulation drugs did not increase the complications of hemothorax in blunt chest wall trauma.…”
mentioning
confidence: 99%